2013
DOI: 10.1128/aem.00698-13
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Coexistence of Distinct Escherichia coli Populations in Various Aquatic Environments and Their Survival in Estuary Water

Abstract: b Escherichia coli, a commensal bacterium from the intestinal tracts of humans and vertebrate animals, has been used as one of two bacterial indicators of fecal contamination, along with intestinal enterococci, to monitor the microbiological quality of water. However, water environments are now recognized as a secondary habitat where some strains can survive. We investigated the survival of E. coli isolates collected from bodies of water in France exhibiting distinct profiles of contamination, defined accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 49 publications
10
109
1
2
Order By: Relevance
“…This suggested the importance of cell strain and origin to their survival in sea water and partially contributed to better understanding of the variations in results of previous studies. Since all tested E. coli strains were exposed to the same environmental conditions, the obtained results probably illustrated the extensive genetic and phenotypic diversity exhibited within E. coli strains, which could explain the different survival abilities in this study and aquatic environments generally [31]. On the basis of genomic information, E. coli species have been divided into eight phylogenetic groups, A, B1, B2, C, D, E, F, and clade I [32].…”
Section: Escherichia Coli -Recent Advances On Physiology Pathogenesimentioning
confidence: 62%
See 1 more Smart Citation
“…This suggested the importance of cell strain and origin to their survival in sea water and partially contributed to better understanding of the variations in results of previous studies. Since all tested E. coli strains were exposed to the same environmental conditions, the obtained results probably illustrated the extensive genetic and phenotypic diversity exhibited within E. coli strains, which could explain the different survival abilities in this study and aquatic environments generally [31]. On the basis of genomic information, E. coli species have been divided into eight phylogenetic groups, A, B1, B2, C, D, E, F, and clade I [32].…”
Section: Escherichia Coli -Recent Advances On Physiology Pathogenesimentioning
confidence: 62%
“…Significant differences in survival in water environment were found among strains belonging to different phylogroups. Recent studies showed that E. coli B1 strains can persist longer in water than strains of the other phylogroups [31] and supported the hypothesis that persistent genotypes have an adaptive advantage in the secondary habitat outside the host [35]. Consequently, once released into water, E. coli strains could be selected on the basis of their survival ability, and the resulting population differed from the original one in terms of phenotypic traits.…”
Section: Escherichia Coli -Recent Advances On Physiology Pathogenesimentioning
confidence: 78%
“…Once released in water, the population structure of E. coli can be modified: it reflects both their primary host and their fate in this environment (Berthe et al, 2013; Chandran and Mazumder, 2015). In environmental water, spatial and seasonal changes of the E. coli population diversity have been demonstrated using fingerprinting methods (Chandran and Mazumder, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, phylogroup B1 isolates are predominantly found in locations with ambient temperature, e.g. soil (Walk et al ., ), on plants (Meric et al ., ), in the gastrointestinal tract of ectotherms (Gordon and Cowling, ), and show prolonged survival times outside the host (Berthe et al ., ). Strikingly, we found that EzeT toxicity is temperature‐dependent and activity is highest at low temperature as described earlier for the GraTA system from the soil bacterium Pseudomonas putida (Tamman et al ., ).…”
Section: Discussionmentioning
confidence: 98%